Analysis of injuries in the Swiss U20 elite ice hockey season 2019/2020 - A retrospective survey - Ruff, J.; Taeymans, J.; Blasimann, A.; Rogan, S. (Sports, 2024)
(1) Background: In Switzerland, there is little data on injury characteristics in elite ice hockey players aged under 20 years (U20 Elite juniors). This study aimed to determine the injury rate and type of injury in Swiss U20 ice hockey players.